CAR-T Cell-Mediated B Cell Depletion in Central Nervous System Autoimmunity. (5th December 2022) - Gupta, Sasha; Simic, Milos; Sagan, Sharon; Duecker, Jason; Shepherd, Chanelle; Sobel, Raymond; Hauser, Stephen; Lim, Wendell; Wilson, Michael; Zamvil, Scott
Abstract : Objective: Evaluate chimeric antigen receptor (CAR)-T cell mediated B cell depletion in experimental autoimmune encephalomyelitis (EAE). Background: CAR-T cells are autologous T cells expressing a non-MHC target antigen specific receptor. We tested whether anti-CD19 CAR-T cells, which more thoroughly deplete human B cell populations than monoclonal antibodies (mAbs), recapitulated the beneficial effects of B cell depletion in EAE. Design/Methods: Anti-CD19 CAR-T cells or control T cells that overexpressed green fluorescent protein were transferred into female wild-type C57BL/6 mice that had been pretreated with cyclophosphamide. EAE was induced by immunization with either recombinant human (rh) myelin oligodendrocyte protein (MOG) (B cell-dependent) or MOG peptide (p) 35-55 (B cell-independent). Mice were evaluated daily for clinical signs of EAE and weekly for peripheral B and T cell counts. B cell levels, T cell immune modulation and histology were assessed at peak disease and at termination. Results: In rhMOG-induced EAE, clinical scores and histologic lymphocyte infiltration were reduced in mice treated with cyclophosphamide and either anti-CD19 CAR-T cells or control T cells. B cell depletion was observed in peripheral lymphoid tissue and in the central nervous system (CNS) of mice treated with anti-CD19 CAR T cells, similar to effects of anti-CD20 mAbs. There was no difference in T cell modulation including Th1 or Th17 populations, but there was a trend towards increase in Treg populations in the periphery and CNS in the anti-CD19 CAR-T cell and control T cell treated animals. Clinical scores and histology did not differ among treatment groups in p35-55-induced disease. Conclusions: Anti-CD19 CAR-T cells thoroughly deplete B cells peripherally and within the CNS. Treatment also results in less severe rhMOG-induced disease, but it was independent of B cell depletion. Our results are consistent with human data indicating that anti-CD19 CAR-T cells deplete B cells across compartments, suggesting that they may hold promise for progressive MS.